2003
DOI: 10.1260/136943303769013219
|View full text |Cite
|
Sign up to set email alerts
|

Tests and Analysis on the Temperature Field within Concrete Filled Steel Tubes with or without Protection Subjected to a Standard Fire

Abstract: The temperature fields within twelve concrete filled steel tubular columns with or without fire protection when exposed to the ISO-834 standard fire curve (ISO-834, 1975) have been experimentally investigated and the results are presented in this paper. The main parameters varied in the tests are: (1)Sectional types, square and circular; (2) Sectional dimensions from 299mm to 800mm; (3) Thickness of fire protection coat from 14mm to 35mm. A derivation has been given for the surface temperature of concrete-fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Based on the finite element model described in Han et al [29] and Lie and Irwin [30], a finite element model was developed to predict the temperature fields in the section of reinforced concrete stub columns as shown in Fig. 4.…”
Section: Thermal Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the finite element model described in Han et al [29] and Lie and Irwin [30], a finite element model was developed to predict the temperature fields in the section of reinforced concrete stub columns as shown in Fig. 4.…”
Section: Thermal Modellingmentioning
confidence: 99%
“…The predicted temperature is a little higher than that of measured results. This may be due to the different conduction analyses developed by Han et al [29] and Lie and Irwin [30] which included convection and radiation effects, however the radiation effect of the electric heating on the thermal conduction is dominant [24].…”
Section: Thermal Modellingmentioning
confidence: 99%
“…However, Tao and Ghannam also noted that the variable emissivity of the steel tube, the moisture content of the infill concrete, and the gap conductance at the steel tube-concrete core interface played potentially important roles in the heat transfer in CFS columns. Han et al [12] presented and modelled the temperature profiles within unprotected and protected CFS columns during 12 furnace tests, although again the density of temperature measurement was low. These tests demonstrated that the spray applied passive fire protection materials used were effective at preventing heat transfer; they also demonstrated that it was possible to predict the steel tube temperatures of the protected CFS sections with reasonable accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…These tests demonstrated that the spray applied passive fire protection materials used were effective at preventing heat transfer; they also demonstrated that it was possible to predict the steel tube temperatures of the protected CFS sections with reasonable accuracy. However, predicting temperatures in CFS sections protected with intumescent coatings continues to prove difficult [12] due to the chemical and physical changes they undergo during heating, foaming, and charring [13].…”
Section: Introductionmentioning
confidence: 99%
“…Wang [10][11] , Zha 12 , Liu 13 and Yin, et al 14 studied fireresisting limit of CFST members by finite element method. Han 15 and Han et al [16][17][18] carried out a series of studies on CFST members through experiments and theoretical analysis. They proposed a method to compute the thickness of fire protection layer that has now been used in the practical design.…”
Section: Introductionmentioning
confidence: 99%